L’ontologia nell’epoca della riproducibilità tecnica del pensiero e della relazione - Pezzano, Giacomo (Mechane, 2021)
This paper starts by acknowledging the growing popularity of the idea that living in the infosphere is producing a reontologization of the world (§ 0), and aims to test such a belief by examining the problem of an ontology of information machines. After explaining the sense in which I use the term “ontology” (§ 1), I discuss the main features of digital ontology and informational ontology: on the one hand, I present the ontological status that information has in digital ontology (§ 2.1) and informational ontology (§ 3.1); on the other hand, I identify the basic characteristics of ICTs that digital ontology (§ 2.2) and informational ontology (§ 3.2) put at the centre of their operation of “symbolic doubling”. Finally, through a comparison with some issues of the continental philosophical tradition, I claim that informational ontology can be considered an ontology at the same time more radical than digital ontology but also weaker, and I conclude by highlighting the difficulties that its conceptual elaboration seems to entail (§ 4).